(untitled) (Indonesian Sports Justice Review, 2024)
Women in Indonesia face enduring gender-based barriers in the sports sector, from underrepresentation in elite competitions to gender stereotypes that restrict their participation in certain sports. This paper explores the role of sports in empowering women and advancing gender justice in Indonesia. Through qualitative interviews with female athletes, sports officials, and gender justice advocates, alongside an analysis of sports policies, the study investigates how gender inequality manifests within the Indonesian sports system. It further explores the ways in which sports can serve as a tool for challenging gender norms, promoting female leadership, and enhancing social mobility for women. By examining both successful and failed initiatives aimed at promoting gender equality in sports, this paper advocates for systemic changes, including gender-sensitive policies, the promotion of women’s sports at all levels, and educational campaigns to combat gender-based discrimination in sports culture.